2013
DOI: 10.4049/jimmunol.1201607
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Caveolin-1 Promotes Hyperinflammation due to Abnormal Heme Oxygenase-1 Localization in Lipopolysaccharide-Challenged Macrophages with Dysfunctional Cystic Fibrosis Transmembrane Conductance Regulator

Abstract: We have previously reported that TLR4 signaling is increased in lipopolysaccharide (LPS) -stimulated Cystic Fibrosis (CF) macrophages (MΦs), contributing to the robust production of pro-inflammatory cytokines. The heme oxygenase (HO-1)/carbon monoxide (CO) pathway modulates cellular redox status, inflammatory responses, and cell survival. The HO-1 enzyme, together with the scaffold protein caveolin 1 (CAV-1), also acts as a negative regulator of TLR4 signaling in MΦs. Here, we demonstrate that in LPS-challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 61 publications
2
62
0
Order By: Relevance
“…mice resulted in a similar lung hyperinflammatory response (8,36). Together, these data suggest that the hyperinflammatory response to acute inflammatory challenges and extensive lung remodeling with chronic inflammation are driven by lack of functional CFTR independent of the class of mutation: null mutations, which are mimicked by the Cftr Ϫ/Ϫ mouse, or class 2 mutations (F508del/F508del).…”
Section: L717mentioning
confidence: 62%
“…mice resulted in a similar lung hyperinflammatory response (8,36). Together, these data suggest that the hyperinflammatory response to acute inflammatory challenges and extensive lung remodeling with chronic inflammation are driven by lack of functional CFTR independent of the class of mutation: null mutations, which are mimicked by the Cftr Ϫ/Ϫ mouse, or class 2 mutations (F508del/F508del).…”
Section: L717mentioning
confidence: 62%
“…Recently, cav-1 has also been implicated as a modulator of inflammation and innate immunity [19,[39][40][41]. It is reported that cav-1 phosphorylation at Tyr 14 following LPS exposure induced the interaction of cav-1 and TLR4, thereby, TLR4 activation of MyD88, leading to the activation of NF-κB and generation of pro-inflammatory cytokines [19].…”
Section: Discussionmentioning
confidence: 98%
“…It is reported that cav-1 phosphorylation at Tyr 14 following LPS exposure induced the interaction of cav-1 and TLR4, thereby, TLR4 activation of MyD88, leading to the activation of NF-κB and generation of pro-inflammatory cytokines [19]. In murine macrophages, cav-1 bound to TLR4 inhibited LPS-induced proinflammatory cytokine (IL-6, IL1β and TNF-α) production [18,41,42], indicating that a cav-1 binding motif in TLR4 is essential for the attenuation of pro-inflammatory signaling. It was reported that TLR4 highly colocalized with cav-1 in caveolae (rafts) fractions in peritoneal macrophages [18] and in human aortic endothelial cells [43].…”
Section: Discussionmentioning
confidence: 98%
“…Macrophages with dysfunctional CFTR show delayed phagolysomal fusion and bacterial clearance after ingestion of Burkhoderia cepacia [52]. CF macrophages also display decreased caveolin-1 expression and enhanced TLR4-dependent responses to LPS [53]. Finally, CFTR deficiency has been reported to induce an intrinsic predisposition of naïve T lymphocytes to differentiate towards a Th17 phenotype [41].…”
Section: Other Dysregulated Immune Pathwaysmentioning
confidence: 97%